EVALUASI PROGRAM SUPERVISI PENGAWAS MADRAS AH DALAM MENINGKATKAN KOMPETENSI MANAJERIAL KEPALA MADRASAH TSANAWIYAH NEGERI DI KOTA BEKASI - Eva Fathyah; Nana Danapriatma; Ibnu Muthi (Jurnal Riset Guru Indonesia, 2022)
This study aims to describe the role of school supervisors in improving the managerial competence of Madrasah principals at MTsN in Bekasi City. The research method uses a qualitative approach with a case study design with interactive model data analysis, and data collection methods using observation, in-depth interviews, and documentation. The results of the study concluded that: 1) Supervisors conduct quality management of madrasah principals in a planned and sustainable manner, 2) Supervisors provide quality development for public relations managerial competencies, and 3) Supervisors guide madrasah principals and teachers to improve integrity and professionalism in implementing function task. While the recommendations from this study, among others. This research method also uses the CIPP method (Context, Input, Process, Product). This method examines from the point of view of the CIPP evaluation that will be used in the evaluation of the madrasa supervisor supervision program. The results of this study are the evaluation of the supervision program for madrasah supervisors in improving the managerial competence of madrasah principals in terms of evaluating the context of the supervisory program. Cooperation between regional stakeholders with the ministry of religion is still hampered by socialization in the form of reporting related to assistance. The evaluation of the inputs has been by the outcome indicators in the aspect of program evaluation related to the availability of human resources. The evaluation of the program implementation process has been by the indicator criteria for the program evaluation results in the aspect of the suitability of the procedural design that has been by the established plan.